1994
DOI: 10.1212/wnl.44.3_part_1.420
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between frontal lobe lesions and Wisconsin Card Sorting Test performance in patients with multiple sclerosis

Abstract: Conceptual reasoning deficits are common in patients with multiple sclerosis (MS) and are typically associated with focal lesions involving the frontal lobes. In this study, we predicted that MS patients with frontal white matter lesions (MS-F) would be more impaired on a standard conceptual reasoning task (Wisconsin Card Sorting Test; WCST) than patients with minimal frontal lesions (MS-NF), even if the total cerebral lesion area (TLA), measured from MRI, was equivalent across groups. We subdivided 43 definit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
119
3
11

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(136 citation statements)
references
References 0 publications
3
119
3
11
Order By: Relevance
“…Neuropsychological defects are associated with progressive more than relapsing disease course (Beatty et al 1988) and MRI evidence of lesion burden and brain atrophy (Amato et al 2004;Benedict et al 2002aBenedict et al , 2004aChristodoulou et al 2003;Rao et al 1989a). Abnormal neuropsychological testing also predicts failures in activities of daily living such as automobile driving (Schultheis et al 2001(Schultheis et al , 2002, employment Rao et al 1991b), success in rehabilitation (Langdon and Thompson 1999), and social skills (Arnett et al 1994;Benedict et al 2001;Knight et al 1997). …”
Section: Comparison With Msmentioning
confidence: 99%
“…Neuropsychological defects are associated with progressive more than relapsing disease course (Beatty et al 1988) and MRI evidence of lesion burden and brain atrophy (Amato et al 2004;Benedict et al 2002aBenedict et al , 2004aChristodoulou et al 2003;Rao et al 1989a). Abnormal neuropsychological testing also predicts failures in activities of daily living such as automobile driving (Schultheis et al 2001(Schultheis et al , 2002, employment Rao et al 1991b), success in rehabilitation (Langdon and Thompson 1999), and social skills (Arnett et al 1994;Benedict et al 2001;Knight et al 1997). …”
Section: Comparison With Msmentioning
confidence: 99%
“…t is well established that MS-associated cognitive impairment is associated with general MRI measures of disease burden such as the total area or volume of T 2 lesions (TLA), [1][2][3][4][5][6][7][8] cerebral volume, 2,7,9 corpus callosum size, 5,7,10 and third ventricle volume or width (3VW). 5,11,12 In contrast, correlations between region-specific pathology on MRI and specific cognitive deficits are rarely reported.…”
mentioning
confidence: 99%
“…5,11,12 In contrast, correlations between region-specific pathology on MRI and specific cognitive deficits are rarely reported. Arnett and colleagues 1 showed that patients with a high ratio of frontal to nonfrontal T 2 lesion area were more likely to exhibit defective performance on the Wisconsin Card Sorting Test, a measure of executive ability. However, this finding was not replicated in a more recent study using different methodology.…”
mentioning
confidence: 99%
“…Increasing recognition of the functional relevance and prognostic role of MS cognitive impairments has resulted in focused attention on MR correlates of cognitive deficit. Assessment of the global and regional white matter (WM) lesion burden, derived from T2-or T1-weighted MRI shows modest association with cognitive status (Arnett et al, 1994;Hohol, et al, 1997;Patti et al, 2009;Rao et al, 1989;Rovaris et al, 2001;Swirsky-Sacchetti et al, 1992). A stronger relationship has been obtained with quantification of the whole and…”
Section: Introductionmentioning
confidence: 99%